Effect of 131I Therapy on Serum Calcitonin Levels in Patients with Graves’ Disease - Földes, J.; Bános, Cs.; Krasznai, I.; Petrányi, Gy., Jr; Steczek, K. (Nuklearmedizin - NuclearMedicine, 1983)
In a group of patients suffering from Graves’ disease a transitory fall of serum calcitonin levels and an increase of triiodothyronine concentrations could be detected after 131I therapy. The transient decrease of the calcitonin values might be related to the high radiosensitivity of the parafollicular cells and to a consecutive impairment of calcitonin production, while the rise of triiodothyronine secretion could be explained by the radiation-induced destruction of the thyroid gland. The drop of serum calcitonin levels lasted for a short period only and did not affect serum Ca concentrations, thus the assumption is highly improbable that the temporarily altered calcitonin secretion involves late consequences for the skeletal system after 131I therapy.